Trends in cardiovascular disease biomarkers and their socioeconomic patterning among adults in the Scottish population 1995 to 2009: cross-sectional surveys - Hotchkiss, Joel William (BMJ Group, 2012)
OBJECTIVES: To examine secular and socioeconomic changes in biological cardiovascular disease risk factor and biomarker prevalences in the Scottish population. This could contribute to an understanding of why the decline in coronary heart disease mortality in Scotland has recently stalled along with persistence of associated socioeconomic inequalities. DESIGN: Cross-sectional surveys. SETTING: Scotland. PARTICIPANTS: Scottish Health Surveys: 1995, 1998, 2003, 2008 and 2009 (6190, 6656, 5497, 4202 and 4964 respondents, respectively, aged 25–64 years). PRIMARY OUTCOME MEASURES: Gender-stratified, age-standardised prevalences of obesity, hypertension, hypercholesterolaemia and low high-density lipoprotein cholesterol blood concentration as well as elevated fibrinogen and C reactive protein concentrations according to education and social class groupings. Inequalities were assessed using the slope index of inequality, and time trends were assessed using linear regression. RESULTS: The prevalence of obesity, including central obesity, increased between 1995 and 2009 among men and women, irrespective of socioeconomic position. In 2009, the prevalence of obesity (defined by body mass index) was 29.8% (95% CI 27.9% to 31.7%) for men and 28.2% (26.3% to 30.2%) for women. The proportion of individuals with hypertension remained relatively unchanged between 1995 and 2008/2009, while the prevalence of hypercholesterolaemia declined in men from 79.6% (78.1% to 81.1%) to 63.8% (59.9% to 67.8%) and in women from 74.1% (72.6% to 75.7%) to 66.3% (62.6% to 70.0%). Socioeconomic inequalities persisted over time among men and women for most of the biomarkers and were particularly striking for the anthropometric measures when stratified by education. CONCLUSIONS: If there are to be further declines in coronary heart disease mortality and reduction in associated inequalities, then there needs to be a favourable step change in the prevalence of cardiovascular disease risk factors. This may require radical population-wide interventions.